External Auditing And Corporate Governance Among Arab Countries: A Review Of The Literature - Fawwaz Ali Taha Ababneh; Nur Hidayah Laili; Khairil Faizal Khairi (ICSRS Publication, 2024)
Non-Indexed Publication